Vasculitis restricted to the lower limbs: a clinical and histopathological study. Issue 4 (26th October 2006) - Khellaf, M; Hamidou, M; Pagnoux, C; Michel, M; Brisseau, J M; Chevallier, X; Cohen, P; Guillevin, L; Godeau, B
Abstract : Background: Rare cases of vasculitis restricted to the lower limbs have been reported, but the characteristics, outcome and response to treatment of this entity are not well known. Objective: To describe the clinical, complementary examinations and response to treatment of this rare entity in the first retrospective series, and to compare data with historical pooled cases. Methods: Retrospective analysis of all biopsy-proven cases observed over a 10-year period in four French tertiary medical units. Diagnosis of vasculitis restricted to the lower limb required the absence of any clinical symptom and complementary test finding, suggesting major extramuscular visceral involvement. Results: 11 patients were included. Vasculitis restricted to the lower limb was associated with disabling muscle pain of the calves. Fever was present in 50% of cases; ankle arthralgia in 50% and skin involvement in 40%. MRI was the cornerstone of the diagnosis, showing hyperintense signal in T2 weight and in T1 weight after gadolinium injection. MRI findings correlated well with clinical outcome and were useful in guiding biopsy. Muscle biopsy was consistent with a polyarteritis nodosa-type vasculitis in only 40% cases, whereas a leucocytoclastic vasculitis was seen for all other cases. Treatment with corticosteroids was effective in all cases, but there were relapses requiring immunosuppressive agents in 54% of cases. Conclusion: Vasculitis of the calf muscles must be considered for patients with calf pain and with a biological inflammatory syndrome.